2002
DOI: 10.1053/rmed.2002.1321
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of adenosine deaminase activity in sputum in pulmonary tuberculosis

Abstract: Eighty-four patients (25 tb, 30 lung cancer and 29 COPD) were included in the study. ADA activity in sputum and serum was measured. Sputum ADA activities of tb patients were significantly higher than the other two groups (P < 0.05). Sputum/serum ADA ratios were similar in all groups. Sputum ADA activities between 150 and 200 U/L were the measurements with the best test performance according to the ROC curve. Sensitivity, specificity, positive predictive value, and negative predictive value were 44.0, 86.4, 57.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…Dilmac¸et al [16] found that sputum ADA activities in tuberculous group were significantly higher than the other two groups (P < 0.01 for lung cancer group, P < 0.05 for COPD) and this coincide with our findings. Also there was a significant increase in serum ADA activities in tuberculous patients than bronchogenic carcinoma and chronic obstructive pulmonary disease patients (P < 0.05) and this also coincide with the present study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Dilmac¸et al [16] found that sputum ADA activities in tuberculous group were significantly higher than the other two groups (P < 0.01 for lung cancer group, P < 0.05 for COPD) and this coincide with our findings. Also there was a significant increase in serum ADA activities in tuberculous patients than bronchogenic carcinoma and chronic obstructive pulmonary disease patients (P < 0.05) and this also coincide with the present study.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with our findings Dimakou et al [14] tried to evaluate the diagnostic value of sputum ADA, ADA1 and ADA2 activity in pulmonary tuberculosis and found that sputum total ADA activity was significantly higher in TB than in lung cancer patients (median 18 U/L [range 3-70] vs. 6 U/L [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]; P < 0.001) respectively and sputum ADA2 activity was significantly higher in TB compared to lung cancer patients (9 U/L [0-65] vs. 5 U/L [0-12]; P = 0.001) respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The developed score did not include other clinical tools that have been employed for the diagnosis of SNPT such as fibrobroncoscopy [9][10][11][12][13], the use of induced sputum [14][15][16][17][18][19][20], concentration techniques [21][22][23][24], auramine-rhodamine enhanced AFB detection [25,26], or Adenosine deaminase activity in sputum or bronchoalveolar lavage [27][28][29][30] or fine needle aspiration [31,32]. Also, the use of liquid media culture was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown an inconclusive result for serum ADA activity in lung cancer (15)(16)(17)(18). In addition, serum tumour markers are not useful in lung cancer diagnosis (1).…”
Section: Introductionmentioning
confidence: 99%